Signal pathways involved in emodin-induced contraction of smooth muscle cells from rat colon - Ma, Tao (World J Gastroenterol, 2004)
AIM: To investigate the effects induced by emodin on single smooth muscle cells from rat colon in vitro, and to determine the signal pathways involved. METHODS: Cells were isolated from the muscle layers of Wistar rat colon by enzymatic digestion. Cell length was measured by computerized image micrometry. Intracellular Ca(2+) ([Ca(2+)]i) signals were studied using the fluorescent Ca(2+) indicator fluo-3 and confocal microscopy. PKCα distribution at rest state or after stimulation was measured with immunofluorescence confocal microscopy. RESULTS: (1) Emodin dose-dependently caused colonic smooth muscle cells contraction; (2) emodin induced an increase in intracellular Ca(2+) concentration; (3) the contractile responses induced by emodin were respectively inhibited by preincubation of the cells with ML-7 (an inhibitor of MLCK) and calphostin C (an inhibitor of PKC); and (4) Incubation of cells with emodin caused translocation of PKCα from cytosolic area to the membrane. CONCLUSION: Emodin has a direct contractile effect on colonic smooth muscle cell. This signal cascade induced by emodin is initiated by increased [Ca(2+)]i and PKCα translocation, which in turn lead to the activation of MLCK and the suppression of MLCP. Both of them contribute to the emodin-induced contraction.